Evaluation of risk of symptomatic cytomegalovirus reactivation in myeloma patients treated with tandem autologous stem cell transplantation and novel agents: a single‐institution study. Issue 6 (5th November 2014) - Marchesi, F.; Pimpinelli, F.; Dessanti, M.L.; Gumenyuk, S.; Palombi, F.; Pisani, F.; Romano, A.; Spadea, A.; Maschio, M.; Ensoli, F.; Mengarelli, A.
Abstract The introduction of proteasome inhibitors and/or immunomodulators in the treatment of myeloma has led to an increase in viral infections, particularly in the Herpesviridae family. Previous studies about the risk of cytomegalovirus (CMV) reactivation after autologous stem cell transplantation (ASCT) have examined the clinical outcome after the first ASCT; however, only 1 study to date has investigated the risk of CMV reactivation after a second transplantation. To address this issue, we performed a retrospective chart review on 78 consecutive myeloma patients (median age 56 years) who underwent a tandem non‐CD34+ selected ASCT after induction treatment with either conventional chemotherapy (n = 42) or with novel agents (n = 36), respectively. All subjects had been mobilized and conditioned with cyclophosphamide plus granulocyte colony‐stimulating factor and melphalan alone, respectively. CMV DNA load in the blood has been determined by polymerase chain reaction in the case of a clinical suspicion of CMV reactivation; therefore, routine monitoring was not performed. Considering the outcome of both the first and the second transplantations, we observed a total of 13 episodes of symptomatic CMV reactivation (13/156, 8%), in 12 subjects (12/78, 15%), all successfully treated. Eight subjects experienced a CMV reactivation after the first ASCT (8/78, 10%); however, only 1 of them (1/8, 12%) experienced a CMV reactivation after the second transplantation. Conversely, 4 CMV reactivations (6%) were observed after the second transplantation in the group of 70 patients who did not experience a CMV reactivation after the first ASCT. No statistically significant difference was observed between first and second ASCT (8/78, 10% vs. 5/78, 6%; P = 0.767). Univariate analysis showed that a pre‐transplant treatment with novel agents was the only baseline factor significantly associated with the occurrence of post‐ASCT CMV symptomatic reactivation after the first transplant (odds ratio [OR]: 9.897; 95% confidence interval [CI]: 1.154–84.840; P = 0.021) but not after the second transplant (OR: 5.125; 95% CI: 0.546–48.119; P = 0.115). No end‐organ disease or primary infection was documented. Our data suggest that second transplantation does not increase the risk of CMV reactivation in our patient population, when compared with the first one, and confirm the role of a pre‐transplant treatment with novel agents as a risk factor for CMV symptomatic reactivation.